2011
DOI: 10.1029/2010jc006883
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of the Mississippi River plume: Impact of topography, wind and offshore forcing on the fate of plume waters

Abstract: [1] High-resolution numerical simulations of the northern Gulf of Mexico region using the Hybrid Coordinate Ocean Model (HYCOM) were employed to investigate the dynamical processes controlling the fate of the Mississippi River plume, in particular the conditions that favor cross-marginal transport. The study focuses on the effects of topography, wind-driven and eddy-driven circulation on the offshore removal of plume waters. A realistically forced simulation (nested in a data-assimilative regional Gulf of Mexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
241
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(248 citation statements)
references
References 61 publications
7
241
0
Order By: Relevance
“…From left to right: t Uwind only ( Figures 1a-1d); F May + t Uwind (Figures 1e-1h); F spring + t Uwind (Figures 1i-1l); F 11 + t Uwind (Figures 1m-1p); May-June NO 3+2 + t Uwind (Figures 1q-1t); May NO 3+2 + t Uwind (Figures 1u-1x). et al, 2011], a persistent west wind reduces the areal extent by ultimately moving the river plume offshore, away from the continental shelf and into deep water [Lentz, 2004;Morey et al, 2003aMorey et al, , 2003bSchiller et al, 2011]. This movement removes the two factors necessary for coastal ocean hypoxia formation: nutrient supply and density stratification.…”
Section: Discussionmentioning
confidence: 99%
“…From left to right: t Uwind only ( Figures 1a-1d); F May + t Uwind (Figures 1e-1h); F spring + t Uwind (Figures 1i-1l); F 11 + t Uwind (Figures 1m-1p); May-June NO 3+2 + t Uwind (Figures 1q-1t); May NO 3+2 + t Uwind (Figures 1u-1x). et al, 2011], a persistent west wind reduces the areal extent by ultimately moving the river plume offshore, away from the continental shelf and into deep water [Lentz, 2004;Morey et al, 2003aMorey et al, , 2003bSchiller et al, 2011]. This movement removes the two factors necessary for coastal ocean hypoxia formation: nutrient supply and density stratification.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the influence of river outflow on shelf waters, a number of studies have observed significant offshore transport events involving Mississippi− Atchafalaya river-influenced waters (Walker et al 2005, Schiller et al 2011, Zhang et al 2012. To date, information about phytoplankton community composition in such offshore river-influenced features is limited to a single event (Wawrik & Paul 2004), and the relationship between environmental conditions and phytoplankton community structure has yet to be examined in such features for different seasons and river discharge conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the Gulf of Mexico, most of the land-sea carbon fluxes are driven by Mississippi River runoff and subsequent biogeochemical organic matter processing that occurs on the Louisiana Shelf near the bird-foot delta, where most of the riverine discharge enters the coastal ocean (e.g., Green et al, 2006). Buoyant freshwater plumes of Mississippi River water generally extend westward from the delta, following the Louisiana coastal current; however, wind-driven changes in the direction of surface water currents near the delta can also lead to an eastward offshore transport of Mississippi River plumes (Schiller et al, 2011).…”
Section: Introductionmentioning
confidence: 99%